Metaverse surgical planning for robotic surgery: preliminary experience and users’ perception - Gabriele Volpi; Cecilia Gatti; Alberto Quarà; Federico Piramide; Daniele Amparore; Paolo Alessio; Sabrina De Cillis; Marco Colombo; Giovanni Busacca; Michele Sica; Paolo Verri; Alberto Piana; et al. (Therapeutic Advances in Urology)
Background: The 3D models’ use for surgical planning has recently gained an ever-wider popularity, in particular in the urological field. Different ways of fruition of this technology have been evaluated over the years. Today, new technological developments allow us to enjoy 3D models in the metaverse. Objectives: The aim of this study is to report the preliminary experience and surgeon’s perception of preoperative planning performed in the metaverse. Design: During the eleventh edition of the Techno-Urology Meeting, all the attendees enjoyed the metaverse experience (META_EXP) for pre-surgical planning of both robot-assisted radical prostatectomy and partial nephrectomy. Users’ perception was then evaluated with the Health Information Technology Usability Evaluation Scale (Health-ITUES) and the Face & Content validity questionnaire. Methods: The 3D virtual models, obtained from standard bi-dimensional imaging, were uploaded on a metaverse platform. Surgeons, thanks to dedicated visors, could plan their surgical strategy immersed in this virtual environment and discuss it with other attendees. Answers to the questionnaires were then evaluated and a stratification was subsequently performed based on surgical expertise, dividing participants in residents (Re), young urologists (YU) and senior urologists (SU). Results: Sixty-six participants filled out the questionnaires. As emerged from the Health-ITUES questionnaire, META_EXP covers an important role in the presurgical/surgical planning and decision-making process and appears to be useful for preoperative planning, with a median response of 4 and 5, respectively. Such results were also confirmed at the Face & Content validity questionnaire, with a median rate of 9/10 regarding its usefulness for surgical planning. Also, anatomical accuracy was positively rated regarding both organ’s and disease’s details, with a median response of 9. Conclusion: In conclusion, the metaverse experience for preoperative surgical planning appears to be useful, user-friendly and accurate. This technology has been widely appreciated by surgeons, irrespective of their experience.